Use of non-nutritive-sweetened soft drink and risk of gestational diabetes. (August 2021) - Nicolì, Francesca; Prete, Alessandro; Citro, Fabrizia; Bertolotto, Alessandra; Aragona, Michele; de Gennaro, Giovanni; Del Prato, Stefano; Bianchi, Cristina
Abstract: In this observational study, we assessed the association between use of non-nutritive-sweetened soft drink (NNSSD) and risk of gestational diabetes (GDM) in 376 pregnant women consecutively screened for GDM, observing that NNSSD consumption is common among pregnant women and is associated with an increased risk of GDM, independently from traditional risk factors.